2009
DOI: 10.3109/11038120903265022
|View full text |Cite
|
Sign up to set email alerts
|

Perceived difficulties using everyday technology after acquired brain injury: Influence on activity and participation

Abstract: Using everyday technology (ET) is a prerequisite for activities and participation at home and in the community. It is well known that persons with an acquired brain injury (ABI) can have limitations in activities of daily living but our knowledge of their difficulties using ET is not known. Thirty-six persons (27 men and 9 women, mean age 44 years, age range 26-60) with an ABI (2-10 years post injury) were interviewed, using the Everyday Technology Use Questionnaire (ETUQ), about their perceived difficulties u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…It is not only assistive devices that are difficult to learn to use. Using everyday technology is also perceived as difficult for pwABI [22,23], as well as accepting help from others, even though it is well known that pwABI benefit from compensatory techniques [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is not only assistive devices that are difficult to learn to use. Using everyday technology is also perceived as difficult for pwABI [22,23], as well as accepting help from others, even though it is well known that pwABI benefit from compensatory techniques [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study (5) found that a majority of individuals with ABI had difficulties using various ET, such as automated telephone services, computer programmes, alarms and cash dispenser. Thus, using ET can be both a demanding and a complicating environmental aspect during the performance of tasks in daily life for people with a cognitive disability.…”
Section: Introductionmentioning
confidence: 99%
“…The voice recorder was also used as a checklist during shopping (4). To overcome the difficulties to take messages during telephone calls, as the participants were not able to keep the information in their memory and record it afterwards, the digital voice recorder was complemented with a telephone pickup that enabled the entire phone call to be recorded (1,4). Thereby, this ET fully matched their needs and abilities.…”
Section: Taking Messages and Recall Information By The Use Of A Digitmentioning
confidence: 99%
“…People with an acquired brain injury (ABI) can experience a wide range of difficulties with daily life tasks, such as self-care, productivity and leisure [1,2], as well as restrictions of participation and decreased quality of life [3][4][5][6][7]. A compensatory approach to reduce remaining disabilities are therefore commonly applied, in rehabilitation in general [4,8,9] as well in occupational therapy [10,11].…”
Section: Introductionmentioning
confidence: 99%